Modern land law - Dixon, Martin (Martin J.); Dixon, Martin (Martin J.). (Milton Park, Abingdon, Oxon [England] : Routledge, 2012)
'Modern Land Law offers a lively and thought-provoking account of a subject that remains at the heart of our legal system. Dispelling any apprehension about the subject's formidability from the outset, this compact textbook provides an absorbing and exact analysis of all the key legal principles relating to land.Written with students firmly in mind, the principal features of this textbook include : a clear introduction to every chapter which frames each topic in its wider context; corresponding chapter summaries which help to consolidate learning and encourage reflection; the use of tables and diagrams to aid understanding of complicated topics; a friendly two-colour text design which complements Martin Dixon's comprehensible and engaging writing; a new companion website which supports this textbook for the first time with a fully customisable testbank for lecturers; self-test questions and practice exam-style questions for students as well as podcasts to keep students updated with new cases, important decisions and other newsworthy issues relating to land law.Updated fully to include discussion of the most recent case law such as Berrisford v Mexfield Housing Association, Halifax v Popeck and Jones v Kernott, Modern Land Law is one of the most current and reliable textbooks available on land law today'--
'Modern Land Law offers a lively and thought-provoking account of a subject that remains at the heart of our legal system. Dispelling any apprehension about the subject's formidability from the outset, this compact textbook provides an absorbing and exact analysis of all the key legal principles relating to land. Written with students firmly in mind, the principal features of this textbook include: a clear introduction to every chapter which frames each topic in its wider context; corresponding chapter summaries which help to consolidate learning and encourage reflection; the use of tables and diagrams to aid understanding of complicated topics; a friendly two-colour text design which complements Martin Dixon's comprehensible and engaging writing; a NEW companion website which supports this textbook for the first time with a fully customisable testbank for lecturers; self-test questions and practice exam-style questions for students as well as podcasts to keep students updated with new cases, important decisions and other newsworthy issues relating to land law. Updated fully to include discussion of the most recent case law such as Berrisford v. Mexfield Housing Association, Halifax v. Popeck and Jones v. Kernott, Modern Land Law is one of the most current and reliable textbooks available on land law today'--
An introduction to modern land law -- Registered land -- Unregistered land -- Co-ownership -- Successive interests in land -- Leases -- The law of easements and profits -- Freehold covenants -- Licences and proprietary estoppel -- The law of mortgages -- Adverse possession.
'First published by Cavendish Publishing as Principles in Land Law in 1994'--T.p. verso.
Includes bibliographical references and index.
Keywords: Land tenure -- Law and legislation -- England; Land tenure -- Law and legislation -- Wales